Plato and democracy today - Lee, Keekok, 1938- (Reith lectures., 2018)
This book deploys an innovative narrative device to mount an exercise in (popular) political philosophy. It presents Plato as "the Reith Lecturer" bringing up to date his critique of democracy which he began more than two thousand years ago in The Republic. --